2013
DOI: 10.4067/s0716-97602013000300002
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile and Qualification of Biological Activity of an Isolated Fraction of Bellis perennis

Abstract: This study describes the isolation and identifi cation of apigenin-7-O-glucopyranoside, a fl avonoid isolated from the fl owers of Bellis perennis L., Asteraceae, an species with a broad spectrum of biological activities. The in vitro antioxidant activity and the inhibition of the enzyme acetylcholinesterase were evaluated. The fl avonoid showed strong in vitro antioxidant potential, because of the capacity of removal of hydroxyl radicals and nitric oxide, and also prevented the formation of thiobarbituric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…Terpenes have been shown to exhibit antioxidant activity in three main ways: through singlet oxygen quenching, through hydrogen transfer, and through electron transfer [48]. The B-ring in flavonoids, which is rich in hydroxyl groups, reacts with superoxide [49]. Some studies have shown that some terpenes regulate the glutamate decarboxylase expression and aspartic and glutamic acid levels in the brain [50] and that the GABA agonist capacity of some flavonoids is related to hydroxyl positions [51].…”
Section: Discussionmentioning
confidence: 99%
“…Terpenes have been shown to exhibit antioxidant activity in three main ways: through singlet oxygen quenching, through hydrogen transfer, and through electron transfer [48]. The B-ring in flavonoids, which is rich in hydroxyl groups, reacts with superoxide [49]. Some studies have shown that some terpenes regulate the glutamate decarboxylase expression and aspartic and glutamic acid levels in the brain [50] and that the GABA agonist capacity of some flavonoids is related to hydroxyl positions [51].…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide reacts with various biological molecules and induces oxidizing product, neuronal toxicity, and epileptic attacks [ 22 ]. Substances with NO-scavenging action compete with oxygen, leading to reduced production of nitrite, showing the antioxidant activity [ 14 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The flavonoids and isoflavonoids are probably electron donors. They have B-ring conjugated chemical structures rich in hydroxyl groups, which have potential antioxidant actions by reacting with and inactivating superoxide anions, oxygen lipid peroxide radicals, and/or stabilizing free radicals involved in the oxidative process by hydrogenation or complexing with oxidant species [ 14 ].…”
Section: Flavonoids With Action In the Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…[70] Experimental studies have shown that, due to their structural similarity with benzodiazepines, flavonoids exhibit antiepileptic effects by modulating the GABA A -Cl-channel complex. [71,72] Overall, avoiding unhealthy diets and adhering to the consumption of flavonoidrich foods can help people have a healthier body. PCs are beneficial nutrients that protect human health by fighting against the free radicals produced in the body cells and preventing oxidative damage.…”
Section: Which Compounds Received More Attention?mentioning
confidence: 99%